2014
DOI: 10.1109/tns.2014.2319098
|View full text |Cite
|
Sign up to set email alerts
|

CUP–A New High-Flux Irradiation Position at the ANITA Neutron Facility at TSL

Abstract: Abstract-A new irradiation position has been constructed, characterized, and put into operation at the ANITA facility in The Svedberg Laboratory (TSL) for accelerated testing of components and systems for single event effects. Results of beam characterization measurements are reported. The energyintegrated neutron flux above 10 MeV, amounting to more than 10 7 cm -2 •s -1 , is the highest among the facilities with atmosphericlike spectra. The employed characterization and simulation techniques are applicable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
(35 reference statements)
2
9
1
Order By: Relevance
“…As CUP is upstream of the collimator the distribution is not circularly symmetric. In the central region the calculated neutron fluence rate above 10 MeV is 7.85 × 10 6 n cm −2 s −1 , compared to 1.17 × 10 7 n cm −2 s −1 from measurements [2]. The present results underestimate measurements at the CUP by 33%.…”
Section: Modellingcontrasting
confidence: 71%
See 2 more Smart Citations
“…As CUP is upstream of the collimator the distribution is not circularly symmetric. In the central region the calculated neutron fluence rate above 10 MeV is 7.85 × 10 6 n cm −2 s −1 , compared to 1.17 × 10 7 n cm −2 s −1 from measurements [2]. The present results underestimate measurements at the CUP by 33%.…”
Section: Modellingcontrasting
confidence: 71%
“…Simulations of a bare spallation target showed qualitative agreement with independent calculations and measurements of the fast neutron field [1]. The present work was motivated partly by a desire to investigate whether improvements to the geometry used in the simulations would lead to closer quantitative agreement with measurements, and partly by a need to extend the work to encompass the new ANITA-CUP facility [2].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The energy-integrated neutron flux above 10 MeV amounts to more than 10 7 cm 2 s 1 with an atmospheric-like spectrum. Characterization measurements have confirmed that the availability of the neutron flux is currently the highest among the facilities of the same class [56]. …”
Section: The Svedberg Laboratory Neutron Facilitymentioning
confidence: 83%
“…The 7 Li target thickness amounted to 4 mm, except for the irradiation with neutron energy of 95.5 MeV, for which the target was 23.5 mm thick [11]. located at the distance 198 cm from the 7 Li target, in socalled Close User Position (CUP) [9].…”
Section: Cross-section Measurementmentioning
confidence: 99%